The Effect of Walking Combined with Neuromuscular Electrical Stimulation on Liver Stiffness and Insulin Resistance in Patients with Non-alcoholic Fatty Liver Disease: An Exploratory Randomized Controlled Trial - IWANAGA, SOHEI; SHIBA, NAOTO; MATSUSE, HIROO; HASHIDA, RYUKI; BEKKI, MASAFUMI; KAWAGUCHI, TAKUMI (Kurume medical journal, 2020)
Increased liver stiffness and insulin resistance are important therapeutic targets in patients with nonalcoholic fatty liver disease (NAFLD). A hybrid training system (HTS) has been developed which combines application of electrical stimulation and volitional contractions. We compared the effect of walking exercise (5.6 km/h) both with and without simultaneous HTS on liver stiffness and insulin resistance. In a single-blind, controlled trial, 32 subjects with NAFLD were randomized to 12 weeks of triweekly 30 minute walking exercise with either HTS (HTS group) or without HTS (control group). Transient elastography for the assessment of liver stiffness, body weight, visceral fat, the homeostasis model assessment of insulin resistance, fasting blood glucose, serum aspartate aminotransferase, alanine aminotransferase, and gamma-glutamyl transpeptidase were evaluated. Data were evaluated using the linear model after adjusting the baseline value. In the subjects with BMI of 27 kg/m2 or more, the decrement of transient elastography in the HTS group was significantly larger than in the control group (mean ± standard error: Δ2.13 ± 0.64 kPa vs. Δ-0.67 ± 0.42 kPa, p=0.0009). There were no significant differences between groups in other endpoints. These results showed that simultaneously combining electrical stimulation with walking exercise could potentially improve liver stiffness in people who have NAFLD. In fact, because the exercise effect was increased by HTS without increasing the walking speed, this HTS could be especially useful for obese or overweight subjects, in whom NAFLD and joint problems often coexist. However, its effects on insulin resistance and body composition were not clear.